Association of a renal papillary carcinoma with a low grade tumour of the collecting ducts. Issue 8 (1st August 2001) - Daniel, L; Zattara-Cannoni, H; Lechevallier, E; Pellissier, J F
Abstract : This case report describes a 75 year old man who had a renal papillary carcinoma associated with a low grade tumour of the collecting ducts. These tumours showed different immunohistochemical patterns for epithelial membrane antigen, cytokeratin 19, and Ulex europaeus lectin expression. In addition, cytogenetic findings were 47, XY, +7 <7> and 45, XY, −8, add(12)(q–ter)<10> for the papillary renal carcinoma and the low grade tumour of the collecting ducts, respectively. This is the first report where these two types of tumour are associated and cytogenetically distinguished.